Sulfated Fucogalactan From Laminaria Japonica Ameliorates β-Cell Failure by Attenuating Mitochondrial Dysfunction via SIRT1–PGC1-α Signaling Pathway Activation - Wu, Nan; Jin, Weihua; Zhao, Yuchen; Wang, Hong; He, Sunyue; Zhang, Wenjing; Zhou, Jiaqiang (Frontiers in Endocrinology, 2022)
As mitochondrial metabolism is a major determinant of β-cell insulin secretion, mitochondrial dysfunction underlies β-cell failure and type 2 diabetes mellitus progression. An algal polysaccharide of Laminaria japonica, sulfated fucogalactan (SFG) displays various pharmacological effects in a variety of conditions, including metabolic disease. We investigated the protective effects of SFG against hydrogen peroxide (H2O2)-induced β-cell failure in MIN6 cells. SFG significantly promoted the H2O2-inhibited proliferation in the cells and ameliorated their senescence, and potentiated β-cell function by regulating β-cell identity and the insulin exocytosis-related genes and proteins in H2O2-induced MIN6 cells. SFG also attenuated mitochondrial dysfunction, including alterations in ATP content, mitochondrial respiratory chain gene expression, and reactive oxygen species and superoxide dismutase levels. Furthermore, SFG resulted in SIRT1–PGC1-α pathway activation and upregulated the downstream Nrf2 and TFAM. Taken together, the results show that SFG attenuates H2O2-induced β-cell failure by improving mitochondrial function via SIRT1–PGC1-α signaling pathway activation. Therefore, SFG is implicated as a potential agent for treating pancreatic β-cell failure.